Glamspark Fever-Bangi / Norshuhada Shaari - SHAARI, NORSHUHADA (2019)
Sobella is a local company that selling a various cosmetic product and Glamspark Fever Bangi is an agent for Sobella's product. The founder of Sobella is Wan Syuhada and has created this product on 2017 and they produced the product at Pengkalan Chepa, Kota Bharu Kelantan